Exploration Of Filosphere Bacteria As Agents Biocontrol Anthracnose Disease Colletotrichum musae (Berk and Curt) Arx On Banana Fruit - Saputri, Indrian Tika; Rianto, Fadjar; Syahputra, Edy (Jurnal Sains Pertanian Equator, 2019)
ABSTRACTColletotrichum musae (Berk. and Curt.) Arx. is a pathogen that causes anthracnose on bananas. Biocontrol agents is one of the alternatives to reduce negative impact of pesticide. This study aims to explore the phylosphere bacteria in bananas which are potential as antagonists to C. musae. The study was carried out at the Laboratory of Plant Diseases, Faculty of Agriculture, University of Tangjungpura Pontianak from November 2017 to April 2018. The bacterial isolates obtained were tested for antagonistic potential against C. musae by dual culture, conidial viability test C. musae and ability to lyse the hyphae. Hypersensitivity testing of bacterial isolates which have the potential as biological agents carried out on tobacco plants. The results of isolation of phylosphere bacteria obtained 16 bacterial isolates. Based on the testing, 3 isolates NPOB1, BPNB1 and BPNB3 have great potential as a antagonists to C. musae. According to antagonistic test, bacterial isolates had an inhibition between 51,84%-65,18%. The inhibition of conidia germination was 4,85%-39,4%. The ability of chitinolytic enzymes produced was 12,43%-31%. Sixteen phylosphere bacteria isolates were not plant pathogenic based on HR tests on tobacco leaves. Keyword : Antagonists, bacteria, Colletotrichum musae, hypersensitivity